Characterisation of Growth Plate Dynamics in Murine Models of Osteoarthritis - Samvelyan, Hasmik J.; Madi, Kamel; Törnqvist, Anna E.; Javaheri, Behzad; Staines, Katherine A. (Frontiers in Endocrinology, 2021)
The purpose of this study was to investigate growth plate dynamics in surgical and loading murine models of osteoarthritis, to understand whether abnormalities in these dynamics are associated with osteoarthritis development. 8-week-old C57BL/6 male mice underwent destabilisation of medial meniscus (DMM) (n = 8) surgery in right knee joints. Contralateral left knee joints had no intervention (controls). In 16-week-old C57BL/6 male mice (n = 6), osteoarthritis was induced using non-invasive mechanical loading of right knee joints with peak force of 11N. Non-loaded left knee joints were internal controls. Chondrocyte transiency in tibial articular cartilage and growth plate was confirmed by histology and immunohistochemistry. Tibial subchondral bone parameters were measured using microCT and correlated to 3-dimensional (3D) growth plate bridging analysis. Higher expression of chondrocyte hypertrophy markers; Col10a1 and MMP13 were observed in tibial articular cartilage chondrocytes of DMM and loaded mice. In tibial growth plate, Col10a1 and MMP13 expressions were widely expressed in a significantly enlarged zone of proliferative and hypertrophic chondrocytes in DMM (p=0.002 and p<0.0001, respectively) and loaded (both p<0.0001) tibiae of mice compared to their controls. 3D quantification revealed enriched growth plate bridging and higher bridge densities in medial compared to lateral tibiae of DMM and loaded knee joints of the mice. Growth plate dynamics were associated with increased subchondral bone volume fraction (BV/TV; %) in medial tibiae of DMM and loaded knee joints and epiphyseal trabecular bone volume fraction in medial tibiae of loaded knee joints. The results confirm articular cartilage chondrocyte transiency in a surgical and loaded murine model of osteoarthritis. Herein, we reveal spatial variation of growth plate bridging in surgical and loaded osteoarthritis models and how these may contribute to anatomical variation in vulnerability of osteoarthritis development.